Listeria monocytogenes Relies on the Heme-Regulated Transporter hrtAB to Resist Heme Toxicity and Uses Heme as a Signal to Induce Transcription of lmo1634, Encoding Listeria Adhesion Protein - dos Santos, Patrícia Teixeira; Larsen, Pernille Tholund; Menendez-Gil, Pilar; Lillebæk, Eva Maria Sternkopf; Kallipolitis, Birgitte Haahr (Frontiers in Microbiology, 2018)
For pathogenic bacteria, host-derived heme represents an important metabolic cofactor and a source for iron. However, high levels of heme are toxic to bacteria. We have previously shown that excess heme has a growth-inhibitory effect on the Gram-positive foodborne pathogen Listeria monocytogenes, and we have learned that the LhrC1-5 family of small RNAs, together with the two-component system (TCS) LisRK, play a role in the adaptation of L. monocytogenes to heme stress conditions. However, a broader knowledge on how this pathogen responds to heme toxicity is still lacking. Here, we analyzed the global transcriptomic response of L. monocytogenes to heme stress. We found that the response of L. monocytogenes to excess heme is multifaceted, involving various strategies acting to minimize the toxic effects of heme. For example, heme exposure triggers the SOS response that deals with DNA damage. In parallel, L. monocytogenes shuts down the transcription of genes involved in heme/iron uptake and utilization. Furthermore, heme stress resulted in a massive increase in the transcription of a putative heme detoxification system, hrtAB, which is highly conserved in Gram-positive bacteria. As expected, we found that the TCS HssRS is required for heme-mediated induction of hrtAB and that a functional heme efflux system is essential for L. monocytogenes to resist heme toxicity. Curiously, the most highly up-regulated gene upon heme stress was lmo1634, encoding the Listeria adhesion protein, LAP, which acts to promote the translocation of L. monocytogenes across the intestinal barrier. Additionally, LAP is predicted to act as a bifunctional acetaldehyde-CoA/alcohol dehydrogenase. Surprisingly, a mutant lacking lmo1634 grows well under heme stress conditions, showing that LAP is not required for L. monocytogenes to resist heme toxicity. Likewise, a functional ResDE TCS, which contributes to heme-mediated expression of lmo1634, is not required for the adaptation of L. monocytogenes to heme stress conditions. Collectively, this study provides novel insights into the strategies employed by L. monocytogenes to resist heme toxicity. Our findings indicate that L. monocytogenes is using heme as a host-derived signaling molecule to control the expression of its virulence genes, as exemplified by lmo1634.